TVET, AI and green HRM for sustainable workforce development: A conceptual framework - Borhan, Nur Amirah; Mohd Bakri, Afiqah; Yahaya, Rusliza; Husin, Azrizal (Journal of Islamic, Social, Economics and Development, 2025)
The global pursuit of sustainable and ethical development has heightened the need for a workforce equipped with Environmental, Social, and Governance (ESG) competencies. In this transformation, Technical and Vocational Education and Training (TVET) institutions play a pivotal role in nurturing talent aligned with the values of environmental stewardship, social responsibility, and economic resilience. However, many TVET systems in developing nations remain underprepared to integrate ESG principles or harness emerging technologies such as Artificial Intelligence (AI) to enhance green skills formation. Grounded in the Resource-Based View (RBV) and Institutional Theory, and guided by the Islamic principles of amanah (trust), khalifah (stewardship), and maslahah (public good), this conceptual paper develops a multi-theoretical framework linking three key drivers, i.e. AI integration in human resource development, ESG-embedded curriculum, and industry–TVET collaboration, with the formation of an ESG-ready workforce, while positing Green Human Resource Management (Green HRM) practices as a moderating factor. This framework offers a holistic understanding of how education and employment ecosystems interact to foster sustainability-oriented talent. By embedding Islamic ethical principles and ESG values in workforce development, the framework contributes to the foundations of ethical, inclusive, and responsible economic growth, particularly relevant to emerging economies such as Malaysia. The paper concludes with policy interventions that can advance sustainable and ethically grounded human capital development in Malaysia and directions for future empirical validation.